Recreation Activities: Art and Crafts to Enhance Elderly’s Self - esteem in Tadcha Villa Community, Bangkok - Metta Choeysombut, เมตตา เชยสมบัติ; Jularat Wattana, จุฬารัตน์ วัฒนะ; วัฒนะ, จุฬารัตน์; เข็มทอง, พนิต (Dusit Thani College Journal, 2018)
The purposes of this research were 1) to develop recreation activities: art and crafts to enhance elderly’s self- esteem in Tadcha Villa Community, Bangkok and 2) to investigate the elderly’s self-esteem before and after attending the recreation activities: art and crafts in Tadcha Villa Community, Bangkok. The specific Quasi-experimental research design employed in this research was one group pretest - posttest design. Data were collected from 24 elderly who voluntarily participated in this research in Tadcha Villa Community, Bangkok. Major research instruments used were 1) the recreation activities: art and crafts, and 2) self–esteem questionnaires. Data were analyzed by using descriptive statistics including frequency, mean, percentage and standard deviation. The results were as: 1) Recreation activities: art and crafts proposed to promote self- esteem in elderly in Tadcha Villa Community, Bangkok were consisted of 4 selected activities through brainstorming of elderly including carving, cooking, basket weaving and molding clay. The activities were implemented through a one-day, 6 hrs training process for each and being completed in 4 weeks continuously. 2) The elderly self-esteem after participated in all the recreation activities in Tadcha Villa Community, Bangkok were of higher values than the values before joining the activities and could be put in order from higher to lower; success, value, important and ability aspects.